2009
DOI: 10.1038/hdy.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression in dioecious populations of the plant Mercurialis annua: comparisons between outcrossed progeny and the progeny of self-fertilized feminized males

Abstract: Inbreeding depression is a key factor in the maintenance of separate sexes in plants through selection for the avoidance of self-fertilization. However, very little is known about the levels of inbreeding depression in dioecious species, obviously because it is difficult to self-fertilize males or females. We overcame this problem by clonally propagating males from lineages in a dioecious metapopulation of the European annual plant Mercurialis annua, feminizing some of them and crossing the feminized with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Reduced viability is often associated with processes such as hybridization and inbreeding (Carr and Dudash 1997, Golmirzaie et al 1998, Melser et al 1999, Busch 2005, Glaettli and Goudet 2006, Eppley and Pannell 2009, Bures et al 2010, or environmental stress such as exposure to high temperature or pollutants (Handique and Baruah 1995, Tretyakova et al 1996, Gottardini et al 2008, Pasqualini et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced viability is often associated with processes such as hybridization and inbreeding (Carr and Dudash 1997, Golmirzaie et al 1998, Melser et al 1999, Busch 2005, Glaettli and Goudet 2006, Eppley and Pannell 2009, Bures et al 2010, or environmental stress such as exposure to high temperature or pollutants (Handique and Baruah 1995, Tretyakova et al 1996, Gottardini et al 2008, Pasqualini et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide values for the relative seed and pollen fertilities of hermaphrodites relative to unisexuals. Previous experiments involving M. annua have shown that inbreeding depression is close to 0 in Iberian populations (i.e., v s is close to 1.0; [19], [37]). Finally, the influence of plant densities on selfing rates ( s ) has been measured across a range of plant densities similar to those used in this study (i.e., we can infer that s was probably around 0.8 and 0.2, respectively, under low densities and high densities in our experiment here [21]).…”
Section: Discussionmentioning
confidence: 84%
“…The fact that hermaphrodites reduced their female reproductive effort in the absence of males could be attributable to the effects of increased selfing and inbreeding depression. However, this seems unlikely, given that Iberian populations of M. annua express almost no inbreeding depression [19], [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although competition probably occurred both above and below ground, it seems plausible that belowground interactions may have been more critical for individuals (here, males) that are known to make heavy demands on their soil environment. Either way, because aboveground biomass is strongly correlated with reproductive output in both males and females of M. annua (Pannell 1997; Eppley & Pannell 2009), effects of competitors on it have clear implications for the plants’ Darwinian fitness.…”
Section: Discussionmentioning
confidence: 99%